Educação profissional técnica de nível médio em música: diálogos entre formação profissional e mundo do trabalho - Félix, Raquel Carmona Torres (2012)
This research has approached the professional technical education of high school level in music. In this context, it has been putting into question the form of a dialogue between professional and technical vocational training in music and the world of work, having as the structuring axis the legislation that has managed and based the technical courses in Brazil. The main objective of this study was to understand how the relationship between professional training and the work world has been established based on the experiences and perspectives of seven students and graduates of the bass guitar, guitar, percussion and saxophone qualifications of the Technical Course of Instrument of School of Music in Federal University of Rio Grande do Norte (EMUFRN). This research was methodologically subsidized by the qualitative perspective. And because is a contemporary phenomenon, the method used was the case study, appropriating documentary sources and participants' testimonies as study techniques. This study has made it possible to understand the participants' musical trajectory, as well as their ways of insertion in the work world and spaces occupied in professional practice, before, during and after the Technical Course. Through analysis based theoretically on professional education, music education, education and sociology, the research has revealed dialogues and counterpoints in the relationship between professional technical training in music and the world of work. Furthermore, it has shown that the legislation that has underpinned the project of the Technical Course of Instrument of the EMUFRN has evidenced the necessity of a professional education that allows the musician to extrapolate the instrumental performance in the world of the present work. It has called into question the education of the “musician artist”, who in the parameters of the legislation, would be in accordance with a scenario that is becoming increasingly dynamic and competitive in the economic world, demanding from the musician not only musical attitudes. Although the research participants are present in the world of work, the study has shown that this performance has evidenced the profile of the musician. This, in turn, is in accordance with the proposal of the vocational training offered. Results aim to contribute to possible problematizations in the field of professional technical education in music and preparation for professional life in the face of the multiplicity of knowledge and practices that involves the professional practice of the musician in the present day.